2002
DOI: 10.1183/09031936.02.00103702
|View full text |Cite
|
Sign up to set email alerts
|

Survey of flexible fibreoptic bronchoscopy in the United Kingdom

Abstract: The practice of flexible bronchoscopy is not standardized. Current guidelines are concerned primarily with safety aspects of the procedure. In view of this, and the authors9 own observations of individual variation in preparation and technique, a national survey of bronchoscopic procedure was performed to assess physicians9 methods. A structured questionnaire was mailed to 547 consultant physicians in adult respiratory medicine. Physicians9 routines of patient preparation, drug therapy, sampling methods, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
108
4
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(129 citation statements)
references
References 34 publications
12
108
4
5
Order By: Relevance
“…More recent studies did not confirm these findings [31,32]. Sedation, in combination with topical anaesthesia and mechanical obstruction from the endoscope, results in hypoxemia [29]. Although we did not routinely apply sedation, a consistent rate of patients (approximately 1/3) in both groups required supplemental oxygen.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…More recent studies did not confirm these findings [31,32]. Sedation, in combination with topical anaesthesia and mechanical obstruction from the endoscope, results in hypoxemia [29]. Although we did not routinely apply sedation, a consistent rate of patients (approximately 1/3) in both groups required supplemental oxygen.…”
Section: Discussionmentioning
confidence: 43%
“…Although there is a debate concerning the need for sedation in FOB [28,29], we always performed non-sedated bronchoscopy with very few exceptions. Rather old studies suggested that sedation was implicated as the cause of major averse events resulting from FOB [3,30].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from the 2000s [4,5] have reported complication rates of 1.08−6.6% and mortality rates of 0.02−0.045%. A large survey in Japan [2] found complication rates ranging from 0.15 to 2.06% and a mortality rate of 0.004%.…”
Section: Discussionmentioning
confidence: 99%
“…In one case, it was caused by brushing of a solitary lesion in a patient with suppurative pneumonia, other deaths were attributed to cerebral infarction caused by air emboli following forceps biopsy of a solitary lesion, aortic dissection following simple bronchoscopy for diffuse lesions, and acute exacerbation of interstitial pneumonia after endobronchial ultrasonography transbronchial needle aspiration of hilar lymph node. Since hemostasis techniques have been improving based on a great deal of experience, fatal case of hemorrhage due to TBLB have not been reported in recent years [2,4,5].…”
Section: Discussionmentioning
confidence: 99%
“…A number of large surveys on bronchoscopic procedures have been performed (2)(3)(4) and numerous guidelines for bronchoscopy have been published worldwide (1,5,6). In 2009, the Japan Society for Respiratory Endoscopy performed a questionnaire survey on bronchoscopy in clinical practice to establish a guideline for painless bronchoscopy (7).…”
Section: Introductionmentioning
confidence: 99%